Perancangan Produk Aksesoris Interior dari Limbah Ampas Kopi dan Sabut Kelapa - Ingrid Payangan; Grace Setiati Kattu (Penerbit Itenas, 2025)
The increase in coffee grounds waste is accompanied by the growing consumption and popularity of coffee, prompting research that results in various innovative products. On the other hand, Indonesia, as one of the largest producers of organic waste in the form of coconut husks, lags behind in waste processing innovation. The purpose of this design is to utilize and create innovative interior accessory products from coffee grounds waste and coconut husks, while assessing the suitability of these waste materials as interior accessories. The design process follows the Design Thinking method, including the stages of Inspiration, Ideation, and Implementation. The outcome of this design is coffee grounds waste and coconut husks becoming a key characteristic accent in decorative lamps, serving as a focal point in interior spaces. These interior accessory products are expected not only to be innovative but also to enhance the aesthetic and functional value of coffee grounds waste and coconut husks as sustainable interior products.